Prioritising patient involvement in patient reported outcome measures– a PROMising way to improve headache care - Lakshini Gunasekera; Jason C. Ray; Neha Kaul; Helmut Butzkueven; Elspeth Hutton; Terence J. O’Brien (The Journal of Headache and Pain)
Abstract Background The optimal management of migraine involves care strategies that reflect what matters most to patients. This usually involves an assessment of treatment efficacy with respect to headache reduction, safety of prescribed medications and overall patient satisfaction and/or improved quality of life. Traditionally, neurologists focus on objective measures such as monthly reductions to headache and migraine days from baseline. This is complemented with various patient reported outcome measures (PROMs) to quantify morbidity and treatment effect from the patient’s perspective. We present a review of currently available headache specific PROMs to summarise the design, key attributes, response format, recall period and length of questionnaires. Methods A literature search was conducted using OVID Medline, Embase and Cochrane Library. The search strategy involved: (satisfaction OR patient satisfaction OR efficacy OR effectiveness) AND (disability OR morbidity OR burden OR severity OR impact OR patient reported outcomes OR PROMs OR outcome measures OR MIDAS OR HIT6 OR HDI OR MSQ OR MIG-SCOG OR Eq. 5D OR WPAI OR PGIC OR quality of life or QOL) AND (migraine OR chronic migraine OR headache OR primary headache OR cephalalgia OR headache disorder). A total of 16,024 articles returned. Removal of duplicates (n = 111), title and abstract screening (n = 15,853) and subsequent full text analysis (n = 19), left 41 articles. Reviewer comments led to addition of further 3 articles to our review. In total, of 44 included articles there were 20 headache-specific PROMs analysed. Results and conclusion Our findings show that there is a significant lack of patient involvement in creation of headache PROMs thus there may be a gap between perceived treatment efficacy from the perspective of neurologists and that of patients. We suggest future assessment of migraine treatment efficacy considers what is important to the patient as a priority, in an effort to improve satisfaction with care.